Peningkatan Keterampilan Mengubah Puisi Menjadi Prosa Di Kelas VI Sekolah Dasar - Putri, Sari Rahma; Zaiyasni, Zaiyasni; Taufina, Taufina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research is to description skill enhancement in change poetry into prose form by used somatic, autiotori, visual, and intellectual (SAVI) model to VI grade elementary school. The research type is PTK by used quality and quantity approach. This research was implemented in SDN 35 Padang City with total 20 students which consist of 9 male student and 11 female student. The score of changing poerty into prose in each pre writing phase in cycle I 76,87 (B), increase in cycle II 90,6 (SB), writing phase in cycle I 68,75 (C) increase in cycle II 90,4 (SB), and on post writing phase cycle I 71,2 (C) increase in cycle II 89,6 (SB).  Keywords: Increased, enhancement in change poetry into prose,SAVI model.